APPLICATION OF QUIZIZZ IN INCREASING STUDENTS’ VOCABULARY OF ELEVENTH GRADE AT SMA NEGERI 1 PEMATANGSIANTAR - Agatha Manurung; Anita Sitanggang; Asima Rohana Sinaga (STAI Darul Qalam Tangerang, 2025)
This research aimed to investigate the effectiveness of using Quizizz, a gamified online learning platform, in improving the vocabulary mastery of eleventh-grade students at SMA Negeri 1 Pematangsiantar. The study employed a quantitative experimental design involving two groups: an experimental group taught using Quizizz and a control group taught through conventional methods. Both groups were given a pre-test and post-test to measure their vocabulary acquisition before and after the treatment. The total number of participants was 72 students, consisting of 36 students in each group, selected using cluster random sampling. The results showed a significant improvement in the vocabulary scores of students in the experimental group compared to those in the control group. The average gain score for the experimental group was notably higher, and the statistical analysis using an independent sample t-test confirmed that the difference was significant (p < 0.05). The findings suggest that Quizizz effectively enhances vocabulary learning by increasing student engagement, motivation, and retention through interactive and enjoyable learning experiences. In conclusion, the study supports the integration of digital tools like Quizizz into vocabulary instruction as a means of improving student learning outcomes. The use of game-based learning not only improves academic performance but also fosters a more engaging and dynamic classroom environment.